Contestation of Discourse on Alcoholism among Native Americans in Joy Harjo’s The Reckoning (2002) - Shofi Mahmudah Budi Utami (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2020)
This study aims at revealing how the discursive practices and the discourse on alcoholism in the Native Americans is produced and contested in a short story entitled The Reckoning by Joy Harjo. The problem in this study is approached by Foucauldian concept of discourse production procedure. The method applied here is the Foucauldian discourse analysis by examining the problem through the process of formation including external and internal exclusion. Central to the analysis is that alcoholism is produced as taboo through the mother character which limits the general understanding about alcoholism; hence this discourse is possible to produce by the subject whose credentials can validate the truth. This discourse is also affirmed by the contextual prohibition which authoritatively can state the truth about alcoholism. This is further contested in the current society of how being an alcoholic would be considered as a non-native American way of life. The result indicates that alcoholism among Native American society becomes the discourse within which constraints produce considerable barriers to expose or address to this topic